THE BENEFITS OF REBOZO TECHNIQUE AND SPLEEN 6 ACUPRESSURE ON THE DURATION OF LABOR IN MULTIPAROUS MOTHERS - Dwi Sulistiyowati; Dewi Mayangsari; Sa'adah Mujahidah; Anita Indra Afriani (Jurnal Smart Kebidanan, 2024)
Labor is a process that ends with the birth of the placenta and baby starting with contractions in the latent and active phases. There are often complications in the process of childbirth, especially in relation to maternal strength, which has an impact on contractions causing prolonged partus, one of the efforts made by pharmacology and non-pharmacology with rebozo and acupressure spleen 6. Pakis Aji Health Center, the number of deliveries in August-October 2021 was 100, of which the most cases were long partus 15 cases (15%). Analyze the effect of rebozo technique and acupressure spleen 6 on the length of labor during stage I in multipa rous mothers at Pakis Aji Jepara Health Center. Quantitative research design with Quasi experimental approach. The population in the study were all maternity mothers as many as 65 respondents and a sample of 60 maternity mothers at the PakisAji Jepara Health Center. It can be concluded that before and after the rebozo technique and acupressure spleen 6 can both increase a significant effect on the length of labor in multiparous mothers in the PakisAji Jepara Health Center, while the difference in the provis ion of rebozo techniques and acupressure spleen 6 has no effect on the length of labor during stage I in multiparous mothers at the Pakis Aji Jepara Health Center.